Pengaruh Pemanfaatan Media Interaktif 3D Terhadap Minat Belajar dan Sikap Ilmiah Peserta Didik Kelas XI MIPA MA As’adiyah Mattirowalie - Musyafira; Muhammad Ali; Nurmi (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2024)
This study aims to determine the effect of 3D Interactive Media Utilization on Learning Interest and Scientific Attitude of Students of Class XI Mipa MA As'adiyah Mattirowalie. The research used is quantitative research with the type of Pre-Experimental Design research with the One Group Pre-Test and Post-Test Design type. The population consisted of 2 classes and sampling was done using purposive sampling technique. The research sample was class XI MIPA with a total of 27 students. The data collection technique used in this study was the administration of pre and post test questionnaires of students' interest in learning and scientific attitudes and documentation. The results of descriptive analysis using a learning interest questionnaire to find out how the learning interest and scientific attitude of students obtained a value that is in the interval 85-100 where the value is categorized as very high. The results of the normality and homogeneity tests obtained normal and homogeneous data results. While the hypothesis test was carried out using paired sample pre-test post-test, the significance value was smaller than 0.05, which was 0.000 where sig (2-tailed) ˂ 0.05. This proves that there is significant effectiveness. This proves that there is significant effectiveness between variables X and Y. The results showed that the use of interactive 3D as a learning resource is effective in increasing students' interest in learning and scientific attitudes.